Nurcholish Madjid’s Contextual Qur’anic Hermeneutics: Epistemology and the Relationship between Religion and State in Indonesia - Fadil Fadil; Jamrud Qomaruz Zaman; Isroqunnajah Isroqunnajah; Siti Aisyah binti Samudin (RUSYDIAH: Jurnal Pemikiran Islam, 2026)
The relationship between Islam and the state in Indonesia’s pluralistic society presents challenges in understanding the teachings of the Qur’an in ways that remain relevant to the socio-historical context without losing their normative dimensions. Within this discourse, Nurcholish Madjid’s thought through contextual Qur’anic hermeneutics is important to examine because it seeks to connect the normative message of revelation with Indonesia’s social and national realities. This research aims to analyze the epistemology of contextual Qur’anic hermeneutics in Nurcholish Madjid’s thought, particularly in understanding the relationship between religion and the state. This is qualitative research using a library research approach. Primary data consist of Nurcholish Madjid’s works, while secondary data comprise relevant academic literature. Data were collected, selected, and verified through comparison across sources, and then analyzed using cultural theme analysis and contextual hermeneutics by connecting socio-historical context, linguistic aspects, interpretive principles, and the moral objectives of the verses. The findings indicate that Nurcholish Madjid’s contextual hermeneutics does not stop at literal meanings but connects historical context, moral messages, and contemporary social realities, as reflected in his interpretation of the concepts of din and Allah. This approach contributes to developing an inclusive understanding of Islam, fostering tolerance, and establishing harmonious relations between religion and the state, with Pancasila as a common national ground. However, contextualization requires epistemological boundaries to ensure that the exploration of the Qur’an’s universal values does not eliminate the specific meanings of the text and the normative principles of Islam.